Effect of physical activity on attention in school-age children with ADHD: a systematic review and meta-analysis of randomized controlled trials - Li, Dong; Li, Lan; Zang, Wanli; Wang, Deng; Miao, Chuyuan; Li, Chenmu; Zhou, Li; Yan, Jin (Frontiers in Physiology, 2023)
Background: Attention problems are one of the core symptoms of Attention-deficit/hyperactivity disorder (ADHD) in children. Previous studies have shown that physical activity intervention has a positive impact on executive function in children and adolescents with ADHD, but there is limited research on attention problems in school-aged children with ADHD. There are still uncertainties about the appropriate physical activity interventions to improve attention problems in this population. This study conducted a Meta-analysis of randomized controlled trials (RCTs) related to physical activity intervention for attention problems in school-aged children with ADHD, providing a certain reference for precise intervention in attention problems for this population. Methods: We systematically searched the following databases up to October 2022: PubMed, Embase, Web of Science, and Cochrane Library, to identify RCTs that investigated the effects of physical activity interventions on children with ADHD. Two investigators independently conducted literature screening, extraction, and quality assessment. We performed a meta-analysis using Stata 15.1. Results: In total, we included 10 studies in this meta-analysis. The results indicated that physical activity intervention had a moderate effect in improving attention problems in school-aged children with ADHD (SMD = −0.48, 95% CI: 0.85, −0.07, p < 0.05). Furthermore, subgroup analysis showed that the effect of physical activity intervention was moderated by intervention type, frequency, and period, rather than the physical activity environment or single intervention time. Conclusion: Our study suggests that cognitively engaging exercise is more effective in improving attention problems in school-aged children with ADHD. Specifically, when cognitive-engaging exercise is used as the type of physical activity and the intervention frequency is less than 3 times per week, with an intervention period of less than weeks, it is most beneficial for improving attention problems in school-aged children with ADHD. However, we should also consider individual differences in children with respect to their ADHD symptoms and accurately evaluate each child’s specific symptoms before intervention. Systematic Review Registration: identifier (CRD42022363255).